Critical Discourse Analysis in the Libyan President Al Ghaddafi’s Last Speech on 22\ 02\ 2011 during the Libyan Uprising. - Lutfi Mohammed Alhemmair Alwash; Mohd Azidan Abdul Jabar; Muhammad Alif Redzuan Abdullah; Vahid NimehchiSalem (USIM Press, 2024)
Vol. 33 No. 3 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences